The experiences of people with haemophilia and their families of gene therapy in a clinical trial setting: regaining control, the Exigency study - Fletcher, Simon; Jenner, Kathryn; Pembroke, Luke; Holland, Michael; Khair, Kate (Orphanet journal of rare diseases, 2022)
Background Gene therapy has the potential to change the life experience of people with haemophilia and family members. Few studies have sought to explore the impact of gene therapy on both individuals and families. The aim of this study was to capture real-life experiences of gene therapy in People with haemophilia and their families. Results Sixteen participants with severe haemophilia (11 haemophilia A, five haemophilia B), mean age 41.4 years (range 23–75 years), took part in a single qualitative interview; ten were accompanied by a family member. Mean time since transfection was 3.56 years (range 1–10 years). Participants saw their involvement in gene therapy as a positive experience, freeing them from the personal burden of haemophilia and furthering treatment options for the wider haemophilia community. However, participants reported being unprepared for the side effects of immunosuppression. Some also reported feeling unsupported and having little control over what was happening as their factor levels became the focus of the process. Conclusion The results suggest that strategies need to be put into place to enable PwH fully to understand the process of gene therapy, and thereby make an informed choice as to whether it is a treatment they might wish for themselves. These include early and ongoing education, increased provision of psychosocial support and ongoing qualitative research.